1992
DOI: 10.1111/j.1476-5381.1992.tb09072.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of treatment with vitamin D3 on the responses of the duodenum of spontaneously hypertensive rats to bradykinin and to potassium

Abstract: 1 The diet of spontaneously hypertensive rats (SHR) and normotensive Wistar-Kyoto (WKY) and Wistar (NWR) rats was supplemented with either 2% calcium lactate in the drinking water or 12.5 jg vitamin D3 100 g-body weight daily by gavage, for 14 days. 2 The blood pressure of the SHR treated with either calcium or vitamin D decreased to the same levels as that of WKY and NWR. 3 The response to bradykinin of the SHR isolated duodenum, which is predominantly contractile, upon treatment with vitamin D (but not with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…3 Studies in spontaneously hypertensive rats have shown decreased blood pressure on oral administration of supplemental vitamin D, as well as improvements in endothelial cell-dependent vasodilation. [5][6][7] Two cross-sectional studies examining vitamin D intake and blood pressure in humans reported conflicting results. Sowers et al examined 86 normotensive young women (20 to 35 years of age) and 222 normotensive older women (55 to 80 years of age).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Studies in spontaneously hypertensive rats have shown decreased blood pressure on oral administration of supplemental vitamin D, as well as improvements in endothelial cell-dependent vasodilation. [5][6][7] Two cross-sectional studies examining vitamin D intake and blood pressure in humans reported conflicting results. Sowers et al examined 86 normotensive young women (20 to 35 years of age) and 222 normotensive older women (55 to 80 years of age).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Oral supplementation with vitamin D lowers blood pressure in hypertensive rats. [5][6][7] In humans, cross-sectional data suggest an association between low vitamin D intake (Ͻ400 IU per day) and higher blood pressure, 8 and a single interventional study in vitamin D-deficient elderly women found that a combination of calcium and vitamin D supplementation had a greater blood pressure-lowering effect than calcium supplementation alone. 9 However, there are no prospective data in the general population that higher vitamin D intake lowers the risk of hypertension.…”
mentioning
confidence: 99%
“…In addition, the risk of incident hypertension was lower in a 4-year prospective study among men and women with higher plasma levels of 25(OH) vitamin D 16. Animal studies have also shown that oral supplementation with vitamin D lowered blood pressure in hypertensive rats; in this model vitamin D inhibited renin expression in the juxtaglomerular apparatus and inhibited smooth muscle proliferation 17-20…”
Section: Introductionmentioning
confidence: 99%
“…20 In the case of the rat mesenteric artery, evidence in the literature suggests that apamin-sensitive Ca 2ϩ -dependent K ϩ channels may be the main ion channels mediating the endothelium-dependent hyperpolarizing response to ACh. 21,22 These channels were found to be impaired in mesenteric vessels 23 as well as in other visceral 24 smooth muscles of the SHR. This could be responsible for the reduced endothelium-dependent hyperpolarizing and relaxation responses to ACh in SHR mesenteric arteries, since the role of NO in the response was well preserved, and the participation of prostacyclin in the relaxation appeared to be insignificant.…”
mentioning
confidence: 98%
“…This could be responsible for the reduced endothelium-dependent hyperpolarizing and relaxation responses to ACh in SHR mesenteric arteries, since the role of NO in the response was well preserved, and the participation of prostacyclin in the relaxation appeared to be insignificant. 11,13,14,18,25,26 Oral administration of cholecalciferol was shown to normalize the blood pressure 4,27 as well as the functioning of Ca 2ϩ -dependent K ϩ channels in SHR visceral 24 and vascular 4 smooth muscles without increasing the serum calcium concentration. 4 We have now investigated the effect of that treatment on the impaired endothelium-dependent relaxation and hyperpolarizing responses to ACh in the isolated mesenteric vascular bed and mesenteric arterial rings of SHR.…”
mentioning
confidence: 99%